Beyond Service Production: Volunteering for Social Innovation. (April 2019) - de Wit, Arjen; Mensink, Wouter; Einarsson, Torbjörn; Bekkers, René
Building on theories from different fields, we discuss the roles that volunteers can play in the generation, implementation, and diffusion of social innovations. We present a study relying on 26 interviews with volunteer managers, other professionals, volunteers, and one former volunteer in 17 (branches of) third sector organizations in eight European countries. We identify organizational factors that help and hinder volunteer contributions to social innovation. While volunteer contributions to social innovations are encouraged by decentralized organizational structures, systematic "scaling up" of ideas, providing training, and giving a sense of ownership, they are hindered by a reluctant attitude and a lack of resources . This rich, explorative study makes it a fruitful start for further research on the relationship between volunteering and social innovation.